MicroRNA-responsive ON-OFF hybrid mRNA switch for precise protein expression control - Kaito Masaki; Yoshihiko Fujita; Hirohide Saito (Molecular Therapy: Nucleic Acids, 2025)
Messenger RNA (mRNA) technology is gaining attention for its potential in developing next-generation therapeutics. However, developing effective protein expression control technologies to regulate mRNA translation, particularly in a cell type- and tissue-specific manner, remains challenging. To achieve enhanced precision in translational regulation, we developed a microRNA (miRNA)-sensing hybrid mRNA switch, integrating an ON-type switch, which activates translation by detecting specific miRNAs expressed in target cells, into an OFF-type switch, which represses translation by sensing another miRNA in non-target cells. We first investigated effective module sequences after the poly(A)-tail for the ON-type mRNA switch to ensure appropriate translational activation in response to target cell-specific miRNAs. Moreover, the hybrid mRNA switch with a dual miRNA-sensing system reduced expression leakage in non-target cells and enhanced ON/OFF selectivity in vitro human cell cultures and in vivo mouse model. This ON-OFF hybrid mRNA switch technology allows for the selective expression of target proteins in designated cells and holds promise for the next generation of mRNA therapeutics.